Audit seasonality and pricing of audit services: Theory and evidence from a meta-analysis. Issue 1 (21st November 2017) - Ng, Hooi Ying; Tronnes, Per Christen; Wong, Leon
Abstract : Auditing is seasonal, with the majority of U.S. public companies having a December fiscal year-end. This results in an audit "busy season" and "off-season" with a non-trivial seasonal impact on the pricing of audit services. We apply an economic framework that explains how audit seasonality affects both the magnitude and the price elasticity of audit demand and audit supply. We find that the audit busy season is associated with an audit fee premium of approximately 10% based on a meta-analysis of 97 analyses from 18 audit fee studies of U.S public companies. A meta-regression of the contextual differences in research design between studies reveals that examining only Big N attenuates the busy season effect size but does not eliminate it, and that the busy season effect size may be larger post-SOX.